Associação do risco cardiovascular, da síndrome da apneia obstrutiva do sono e da qualidade de vida em pacientes com DHGNA - Baião, Kennia Maria Rocha (2018)
Non-Alcoholic Fatty Liver Disease (NAFLD) is characterized by accumulation of lipids in hepatocytes, which accounts for at least 5% of the weight of this tissue. It affects patients in different age groups; these tend to present hepatic alterations characterized not only by the accumulation of fat but, in some cases, also by the presence of inflammation and fibrosis, even evolving to cirrhosis. It is considered the hepatic component of Metabolic Syndrome (MS) and this, in turn, is also an inducer of NAFLD. The present study proposes to evaluate the degree of steatosis in patients with NAFLD and their relationship with cardiovascular risk, the prevalence of OSAS and quality of life. This is a cross-sectional study, where 173 patients were interviewed at the outpatient clinic. Hepatology, which is a reference service of the State, University Hospital of the Federal University of Sergipe. Socio-demographic data and anthropometric measurements, results of biochemical laboratory tests and image of medical records were collected, and these patients were submitted to quality of life (QOL) questionnaires (WHOQOL bref), CVD risk (Framinghan score), individual risk of OSAS (Berlin scale) and bioimpedance test. We obtained as results a prevalence in the low risk population to develop CVD (58.4%), a prevalence of the sample for high risk of OSAS (64%), the QV assessment showed better results in the psychological and social relations domains . We conclude that there is an association between the degree of NAFLD and the evolution of OSA in the patients studied. There was no association with the increase in the risk of CVD, and when we assessed the association with the QOL, there was no significant difference between the total score quality of life in patients with mild steatosis for individuals who presented them in marked form. Thus, we emphasize the importance of the global evaluation of these patients, from the beginning of the detection of NAFLD.